Executive compensation : the finance perspective - Vieito, João Paulo (2015)
This paper is a survey of the research on executive compensation from the period between 1995 and 2007, focusing on the most important academic publications in the area. The reason for analysing this period of time and these publications is that we believe that 13 years is enough time to cover a set of research studies that are representative of the present lines of investigation on this theme, and that the most important findings in terms of executive compensation are published in these high quality scientific publications